Comparative genomics analysis of the reason for 12C6+ heavy-ion irradiation in improving Fe3O4 nanoparticle yield of Acidithiobacillus ferrooxidans - Jiani Yang; Shuang Zhang; Lirong Geng; Dan Zhao; Siyu Xing; Xinyue Ji; Lei Yan (Ecotoxicology and Environmental Safety)
The Fe3O4 nanoparticle synthesized by Acidithiobacillus ferrooxidans have a broad practical value, while the low yield limits their commercial application. Herein, we employed a 12C6+ heavy-ion beam to induce mutagenesis of A. ferrooxidans BYM and successfully screened a mutant BYMT-200 with a 1.36 mg/L Fe3O4 nanoparticle yield, which could stably inherit over many generations based on assessing cell magnetism and Fe3O4 nanoparticle synthesis. Comparative genome analysis detected 14 mutation sites, causing six synonymous mutations, one missense mutation, and one nonsense mutation. We further annotated the genes involved in the mutation, such as hcp, hsdM, yghU, K7B00_11365, and K7B00_11355, which are responsible for the substantial changes in the Fe3O4 nanoparticle yield of A. ferrooxidans. Additionally, we performed a pan-genome analysis to understand how these genes regulate Fe3O4 nanoparticle synthesis. The core genome of 2376 orthologous clusters was identified and visualized by progressive Mauve alignment and OrthoVenn. A total of 109 regulatory genes related to iron metabolism were identified, mainly involved in electron transport, iron acquisition, iron storage, and oxidative stress. The mutant genes are closely related to iron-sulfur clusters and oxidative stress. Accordingly, we proposed a hypothetical mechanism for increasing Fe3O4 nanoparticle production in A. ferrooxidans BYMT-200 to withstand high oxidative stress caused by heavy ion radiation. Our study offers significant theoretical guidance for further acquiring the high-yield Fe3O4 nanoparticle-producing bacteria and studying the mechanism of its synthesis.